Synthesis of nanostructured ThO2 pellets. Issue 7 (25th February 2019) - De Bona, Emanuele; Walter, Olaf; Störmer, Heike; Wiss, Thierry; Baldinozzi, Gianguido; Cologna, Marco; Popa, Karin
Abstract: We present here for the first time the production of 3‐ to 5‐nm–sized thoria nanopowders by decomposition of Th‐hydroxide under hot compressed water and their consolidation by high‐pressure spark plasma sintering into dense nanostructured ThO2 with grain size of 50 nm.